EVALUASI PROGRAM KELURAHAN TANGGUH BENCANA (KATANA) DI KOTA SEMARANG - Serenta Pelprii Trimegah; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
Indonesia, as a country with high disaster vulnerability, requires effective disaster management strategies that reach the lowest administrative level. One of the government’s efforts to strengthen community resilience is the Kelurahan Tangguh Bencana (KATANA) Program implemented by the Regional Disaster Management Agency (BPBD). This study aims to evaluate the implementation of the Katana Program in Semarang City using William N. Dunn’s policy evaluation framework and to analyze its impact on improving disaster mitigation capacity and community resilience. The research adopted a qualitative approach with data collected through in-depth interviews, participatory observation, and document analysis. The study focused on three kelurahan with different resilience levels Kelurahan Gajahmungkur (Utama level), Kelurahan Meteseh (unclassified), and Kelurahan Rowosari (Pratama level) as well as the BPBD of Semarang City. The findings reveal that the Katana Program has contributed to enhancing community knowledge, preparedness, and social cooperation. However, its implementation still faces several challenges, particularly limited funding, suboptimal coordination among stakeholders, and uneven community participation across kelurahan. This study concludes that although the program has laid a foundation for local resilience, strengthening institutional arrangements, improving human resource capacity, and optimizing community participation are necessary to make the Katana Program more effective, efficient, and sustainable in Semarang City.